2021
DOI: 10.1038/s41398-021-01213-0
|View full text |Cite
|
Sign up to set email alerts
|

1q21.1 distal copy number variants are associated with cerebral and cognitive alterations in humans

Abstract: Low-frequency 1q21.1 distal deletion and duplication copy number variant (CNV) carriers are predisposed to multiple neurodevelopmental disorders, including schizophrenia, autism and intellectual disability. Human carriers display a high prevalence of micro- and macrocephaly in deletion and duplication carriers, respectively. The underlying brain structural diversity remains largely unknown. We systematically called CNVs in 38 cohorts from the large-scale ENIGMA-CNV collaboration and the UK Biobank and identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 70 publications
(81 reference statements)
1
20
0
1
Order By: Relevance
“…There are no obvious J o u r n a l P r e -p r o o f patterns recurrently observed across all CNVs but some regions appear to be more frequently affected: insula, cingulate, dorsolateral prefrontal cortex, inferior frontal gyrus, orbitofrontal cortex, supplementary motor cortex, postcentral gyrus, superior parietal area, fusiform gyrus, and superior temporal area. The few studies reporting Cohen's d for regional alterations showed moderate to large effect sizes (absolute Cohen's d ranging from 0.5 to 1.3 in 16p11.2 proximal and 22q11.2) (29,30,35,36), which is in stark contrast with the small effects (absolute Cohen's d <=0.20 (32,34)) in SCZ and ASD.…”
Section: Regional Effects On the Cortexmentioning
confidence: 86%
See 1 more Smart Citation
“…There are no obvious J o u r n a l P r e -p r o o f patterns recurrently observed across all CNVs but some regions appear to be more frequently affected: insula, cingulate, dorsolateral prefrontal cortex, inferior frontal gyrus, orbitofrontal cortex, supplementary motor cortex, postcentral gyrus, superior parietal area, fusiform gyrus, and superior temporal area. The few studies reporting Cohen's d for regional alterations showed moderate to large effect sizes (absolute Cohen's d ranging from 0.5 to 1.3 in 16p11.2 proximal and 22q11.2) (29,30,35,36), which is in stark contrast with the small effects (absolute Cohen's d <=0.20 (32,34)) in SCZ and ASD.…”
Section: Regional Effects On the Cortexmentioning
confidence: 86%
“…Neuroimaging features associated with 15q11.2 deletion may mediate between 4 to 10% of the cognitive effects of this CNV (47). Similarly, alterations of Total-SA and ICV accounted for 5 to 17% of some cognitive deficits in 1q21.1 distal carriers (36). In Williams-Beuren syndrome, a study on 22 CNV carriers suggested that the neuroanatomical profile mediated cognitive impairments and hyper-sociability (66).…”
Section: Do Brain Alterations Mediate Effects On Cognition and Behavior?mentioning
confidence: 98%
“…A common finding across all four CNVs studied by the 22q11-ENIGMA and ENIGMA-CNV WGs is the presence of a gene dosage response on several brain structures (Sønderby et al, 2021;Lin et al, 2017;Sønderby et al, 2018;van der Meer et al, 2020) (Chawner et al, 2019). The general rule seems to be that the effect on brain structure fits an additive model for gene dosage formed by, for example, gene expression, whereas an inverted U-shaped effect curve is observed for the phenotype (Deshpande & Weiss, 2018).…”
Section: Summary and Implications Of The Findingsmentioning
confidence: 97%
“…The pathogenic CNVs at the eight target loci in this study are not limited to schizophrenia only; they are also pathogenic with other neurodevelopmental disorders and psychiatric conditions. For example, CNVs at 1q21.1 are associated with attention-deficit hyperactivity disorder, oppositional defiant disorder, anxiety disorder, autism spectrum disorder, tic disorder, intellectual disability, and depression [ 10 , 34 , 35 , 36 ]. The microdeletion of NRXN1 at 2p16.3 is associated with several neurodevelopmental disorders and intellectual disability, too [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, to study pathophysiology and neuropsychiatric manifestations of the rare pathogenic CNVs associated with psychiatric disorders, two working groups were formed by the Enhancing NeuroImaging Genetics through Meta-Analysis (ENIGMA) consortium formed: the ENIGMA 22q11.2 Deletion Syndrome Working Group (22q-ENIGMA WG) and the ENIGMA-CNV Working Group (ENIGMA-CNV WG) [ 7 ]. These two working groups have reported the effects of several rare pathogenic CNVs, including 22q11.2 [ 7 ], 16p11.2 distal [ 8 ], 15q11.2 [ 9 ], and 1q21.2 [ 10 ], on brain structure, cognition, and neuropsychiatric symptoms, which has increased our understanding of the genetic etiology and neurobiology of schizophrenia and related psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%